Pengaruh Dua Macam Perlakuan Mikroorganisme terhadap Kemudahan Degradasi Poliuretan Hasil Sintesis dari Monomer Polietilen Glikol Berat Molekul 400 dengan Metilen-4,4â- difenildiisosianat - E. Rohaeti; N. M. Surdia; C. L. Radiman; E. Ratnaningsih (Journal of Mathematical and Fundamental Sciences, 2004)
Degradation of polyurethane sheets using two types of microorganism treatment has been carried out. In this research, the polyurethane sheets were prepared by polyethylene glycol with a molecular weight of 400 and methylene-4,4'-diphenyldiisocyanate at room temperature, followed by heat-pressed at temperature of 180oC. Characterization of polyurethane sheets was based on functional groups using Fourier Transform Infra Red spectrophotometry and thermal properties using Differential Thermal Analysis, and also for physical properties using X-Ray Diffraction. Degradation treatment was carried out by exposing polyurethane to activated sludge and compared to Pseudomonas aeruginosa in a Luria Bertani liquid media at 37oC. The variation of incubation time was 5, 10, 15, 20, 25, and 30 days, respectively with changes of media every 5 days. After degradation, weight loss of polyurethane sheets was determined. The result showed that polyurethane was biodegradable, although at different degradation rate. Weight loss of polyurethanes by activated sludge was higher than by Pseudomonas aeruginosa. Thus, activated sludge was more effective than Pseudomonas aeruginosa in degradating polyurethane. Identification with X-Ray Diffraction showed that degradation decreased the degree of crystallinity of the polyurethane material. Fourier Transform Infra Red spectra after degradation showed that the specific peak for the urethane group disappeared. Variation of the incubation time showed that the polyurethane product had the highest weight loss during the first five days.